The Effect of Self-Care Program Education Based on Orem's Theory on Mental Aspect of Quality of Life in Multiple Sclerosis Patients - Reza Masoudi; Iesa Mohammadi; Fazlollah Ahmadi; Ali Hasanpour-Dehkordi (Iran University of Medical Sciences, 2009)
Background and Aim: Multiple sclerosis is a chronic and degenerative disease of the central nervous system, frequently occurs in young people, affecting their quality of life. The aim of the study was to examine the effect of self- care program education based on Orem's theory on mental aspect of quality of life in multiple sclerosis patients.   Material and Method: This quasi-experimental study was done on 70 multiple sclerosis patients. The experimental group was treated with 8 educational sessions about self-care based on Orem's theory and was compared with the control group.   Results: The findings showed that before intervention, the quality of life score in mental aspect was not statistically different between the two groups (P= 0.33), while after intervention a statistically significant difference was seen between the two groups (P= 0.001). Pair t test showed a statistically significant difference in experimental group between before and after self care performance (P= 0.001), whereas, the same test showed no statistically significant difference in control groups (P= 0.86).   Conclusion: Designing and utilizing a self care program based on Orem's theory could be effective on mental aspect of quality of life in multiple sclerosis patients. Therefore, if a program is designed on the basis of educational needs and with respect to training the patient and the "Orem self- care model" approach, it might be effective for enhancing the quality of life in mental aspect among multiple sclerosis patients.